Accelerating Post-Pandemic Recovery: The Strategic Role Of Civil Society In Bali - Gede Indra Pramana (Pusat Riset Politik BRIN, 2023)
Since 2019, the COVID-19 pandemic has given significant impacts to people's lives. The order of the community's social life—in terms of economic, social, political, and cultural—has experienced significant changes in its efforts to deal with the pandemic. Besides impacting public health, the economic downturn due to the pandemic has put pressure on society. Most people in Bali, who economically relied on the tourism sector, nonetheless felt a much greater impact during this time. After nearly two years of dealing with the pandemic, people demand a change in the way of life through great societal adjustments for their recovery. The state's strengthened role was not enough to mitigate this situation. At this point, civil society has a strategic role in accelerating the recovery of people's social life. This paper argues that civil society can play an important role in helping the recovery of social life and the economic sector of citizens. Therefore, this research seeks to examine the strategic role of civil society after the COVID-19 pandemic in Bali using the case study method. Data was collected through semi-structured interviews and observations with key civil society actors. Learning from the Bali case, this research shows that the civil society has great potential in overcoming the COVID-19 pandemic.